Analysis of correlates and predictors of conflict management styles of college and university administrators in Bangkok - Chinnamethipitak, Kesorn (Animo Repository, 1989)
This study analyzes the conflict management styles of the top and middle level college and university administrators in Bangkok and identifies the significant correlates and predictors of their choice of conflict management styles. The study made use of the descriptive-normative correlational method of research. It was concerned with the gathering of data concerning variables of interest as they applied to the administrators included in the study, and to identify the factors related to and predictive of the respondents' choices of conflict-handling styles. The instruments used in the study were the Administrator Information Questionnaire, to elicit information concerning the administrators' sex, age, marital status and other administrator-related variables the Thomas-Kilman Conflict Mode Instrument, to determine the predominant conflict-handling styles of respondents, and the Situational Conflict Handling Styles to determine the appropriateness of the respondents' use of conflict-handling styles. Multiple correlation and multiple regression analysis were used for the treatment of the data. The study found out that Thai college and university respondent administrators have high use of the avoiding style and the collaborating styles of conflict management, and an average use of compromising and accommodating styles. They are generally unassertive and tend to minimize the use of the competing style of conflict management. They tend to exercise discretion in confronting issues and prefer to maintain pleasant relationships. Significant differences were found to exist in the administrators' choices of conflict-management styles. Demographic, employment-related, and cultural-related variables significantly influence conflict management styles of administrators. The study also showed that the best predictors of administrators' choices of conflict management are tenure for competing style sex for collaborating style, nationality for compromising style frequency of travel outside of country for avoiding style and tenure and type of institution's ownership for accommodating style. Given actual conflict situations, administrators are generally able to choose the appropriate conflict-management styles. Therefore based on the findings, Thai administrators in higher educational institutions are generally unassertive, tend to advocate harmonious relationships and exercise discretion in confronting conflicts. Conflicts are mostly resolved through consensual decision. Second, Thai administrators' choices of conflict-handling styles are dependent on sex, age, administrative experience and tenure, frequency of travels outside the country, and nationality. Third, the choice of conflict-handling styles of Thai administrators can be predicted on the basis of selected personal, school, and cultural variables. Fourth, since the factors analyzed in the study explained about 2 percent only of the variance in the administrators' conflict-handling styles, there are other variables which may be significantly related with the given dependent variable. Lastly, the Thomas-Kilman Conflict Mode Instrument is applicable for use in the Thai setting.